Lignin‐retaining porous bamboo‐based reversible thermochromic phase change energy storage composite material. (2nd March 2020) - Heng, Yingqi; Feng, Nianrong; Liang, Yexin; Hu, Dongying
Summary: Shaped‐stabilized reversible thermochromic phase change materials of (TBC‐LB, TBB‐LB) were assembled by impregnation the TBC (crystal violet lactone/bisphenol A/tetradecanol) or TBB (3, 3′‐Bis (1‐n‐octyl‐2‐methylindol‐3‐yl) phthalide/bisphenol A/tetradecanol) into lignin‐retained bamboo (LB) for energy storage. Analysis of the chemical structure of lignin‐retained wood showed that the removal of part of lignin from the bamboo contributes to the penetration of the compound, and the partial retention of lignin is advantageous for maintaining high mechanical properties. The SEM micrographs of TBC‐LB and TBB‐LB indicate that TBC and TBB are well immersed into the porous LB. The TBC‐LB showed an endothermic peak at 40.8°C with Δ H m of 113.3 J g −1 and two exothermic peaks at 28.8°C and 21.9°C with Δ H L+S of 110.2 J g −1, and the value is basically equal to the pure TBC compound, indicating that TBC has been fully immersed in LB to form a composite phase change material. For phase change latent heat and melting‐cooling temperature, TBB‐LB and TBC‐LB showed the same trend. About 100 heating‐cooling cycles were performed to evaluate the reliability of TBC‐LB and TBB‐LB, showing excellent cycle stability. It is foreseen that the prepared shape‐stable TBC‐LB and TBB‐LB have great potential for applying insulation systems in reversible thermochromic phase change energy storage. Abstract : In this study, shaped‐stabilized reversible thermochromic phase change energy storage materials of (TBC‐LB, TBB‐LB) were assembled by impregnation the crystal violet lactone‐based TBC or 3, 3′‐Bis (1‐n‐octyl‐2‐methylindol‐3‐yl) phthalide‐based TBB into lignin‐retained bamboo (LB). The TBC‐LB and TBB‐LB showed high latent heat values which are very close to the pure TBC and TBB compound, indicating that TBC and TBB were well impregnated into LB to form a composite phase change material. The prepared shape‐stabilized TBC‐LB and TBB‐LB have considerable potential for application of insulation system in reversible thermochromic phase change energy storage.